Pengaruh Kesadaran Wajib Pajak dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan - Ririn Widia Astuti; Anisa Sains Kharisma; Roni; Dumadi; Nasiruddin (Journal of Accounting and Finance (JACFIN), 2019)
This paper aims to find out the influence of taxpayer awareness, tax sanctions on taxpayer compliance in paying Land and Building Tax (PBB) in Teggongan Village. The sample used was 85 respondents. The data used is primary data in the form of distributing questionnaires to all residents of Tegongan Village who are taxpayers. The analytical tool used in this study used a data quantity test tool in the form of validity and reability tests and hypothesis tests in the form of multiple linear regression tests. The results showed that taxpayer awareness does not affect taxpayer compliance in paying land and building taxes, tax sanctions affect taxpayer compliance in paying land and building taxes, taxpayer awareness and tax sanctions jointly affect taxpayer compliance in paying land and building taxes in Teggongan Village